Association between the time after transplantation and different immunosuppressive medications with dental and periodontal treatment need in patients after solid organ transplantation. Issue 2 (21st February 2018) - Schmalz, Gerhard; Wendorff, Horst; Berisha, Lisa; Meisel, Anja; Widmer, Florian; Marcinkowski, Anna; Teschler, Helmut; Sommerwerck, Urte; Haak, Rainer; Kollmar, Otto; Ziebolz, Dirk
Abstract: Objective: The aim of this study was to investigate the association of time after transplantation and different immunosuppressive medications with dental and periodontal treatment needs in patients after solid organ transplantation (SOT). Methods: After lung, liver, or kidney transplantation, patients were included and divided into subgroups based on the time after SOT (0‐1, 1‐3, 3‐6, 6‐10, and >10 years) and immunosuppression (tacrolimus, cyclosporine, mycophenolate, glucocorticoids, sirolimus, and monotherapy vs combination). Dental treatment need was determined by the presence of carious lesions, while periodontal treatment need was diagnosed based on a Periodontal Screening index score of 3‐4. The overall treatment need included both the dental and/or periodontal treatment needs. Statistical analysis was performed using the Kruskal‐Wallis test and chi‐squared test ( P < .05). Results: A total of 169 patients were included after SOT. A dental treatment need of 44%, a periodontal treatment need of 71%, and an overall treatment need of 84% were detected in the total cohort. Only patients with >10 years after SOT had a lower dental treatment need compared to the other groups ( P = .02). All other comparisons of dental, periodontal, and overall treatment needs were comparable between subgroups depending on time since SOT. Furthermore, no statistically significant differences were found in terms of the dental, periodontal, or overall treatment needs following the administration of different immunosuppressive medications. Conclusion: The high treatment need of patients after SOT, irrespective of the time since transplantation, suggests insufficient dental and periodontal treatment before and maintenance after organ transplantation. Furthermore, immunosuppressive medication was not associated with the treatment need.